A System for the Diagnosis, Placement, and Prosthetic Restoration of Root Form Implants (U.S. Patent #5,769,636)v - Francesco D’Aiuto (Journal of Prosthodontics, 2003)
It is difficult to achieve a high degree of reproducibility when using a diagnostic wax-up as the template for fabrication of a definitive implant restoration.